A Black Cartographer of the Long Eighteenth Century: Anastácio de Sant’Anna’s Guia de Caminhantes - Matthew Francis Rarey (Arts)
From 1816 to 1817, Anastácio de Sant’Anna, a pardo (mixed-race) artist and cartographer active in Salvador, Bahia, Brazil, produced the Guia de Caminhantes, a manuscript atlas of Brazil and the Americas. Sant’Anna’s Guia is one of the few extant cartographic works produced by a Black artist during the slavery era. Discussing the Guia in English for the first time, this essay positions Sant’Anna’s work inside of the emergent subfield of Black Geographies. It argues that Sant’Anna used the Guia to advocate for the place of Black and Indigenous histories in Brazil’s nascent, post-colonial national identity, while also interrogating the history of cartography and landscape painting in colonial Brazil.